2005
DOI: 10.1161/01.res.0000185823.73556.06
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Monophosphate-Activated Protein Kinase Suppresses Vascular Smooth Muscle Cell Proliferation Through the Inhibition of Cell Cycle Progression

Abstract: Abstract-Vascular smooth muscle cell (VSMC) proliferation is a critical event in the development and progression of vascular diseases, including atherosclerosis. We investigated whether the activation of adenosine monophosphate-activated protein kinase (AMPK) could suppress VSMC proliferation and inhibit cell cycle progression. Treatment of human aortic smooth muscle cells (HASMCs) or isolated rabbit aortas with the AMPK activator 5-Aminoimidazole-4-carboxamide ribonucleoside (AICAR) induced phosphorylation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
153
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(173 citation statements)
references
References 45 publications
(55 reference statements)
18
153
1
Order By: Relevance
“…Furthermore, the present study revealed that the phosphorylation of endogenous p53-Ser 15 was increased by LKB1 overexpression or AMPK activation, suggesting that p53-Ser 15 phosphorylation, a modification essential for p53 stabilization, may be involved in p21/WAF1 upregulation. The results of the present study are consistent with previous reports indicating that AMPK induces phosphorylation of p53-Ser15 in hepatoma HepG2 cells (21), mouse embryonic fibroblasts (22), human aortic smooth muscle cells and rabbit aortic strips (23). Other kinases have been demonstrated to phosphorylate p53 at Ser 15 , including ATM and ATR serine/threonine kinases, as they also target p53 at this site (24).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the present study revealed that the phosphorylation of endogenous p53-Ser 15 was increased by LKB1 overexpression or AMPK activation, suggesting that p53-Ser 15 phosphorylation, a modification essential for p53 stabilization, may be involved in p21/WAF1 upregulation. The results of the present study are consistent with previous reports indicating that AMPK induces phosphorylation of p53-Ser15 in hepatoma HepG2 cells (21), mouse embryonic fibroblasts (22), human aortic smooth muscle cells and rabbit aortic strips (23). Other kinases have been demonstrated to phosphorylate p53 at Ser 15 , including ATM and ATR serine/threonine kinases, as they also target p53 at this site (24).…”
Section: Discussionsupporting
confidence: 93%
“…As AMPK phosphorylation has been linked to inhibition of SMC proliferation (Nagata et al 2004, Igata et al 2005, activation of AMPK would not be expected if adiponectin and globular adiponectin stimulate SMC proliferation. On the other hand, AMPK phosphorylation occurred upon treatment with PDGF, a potent mitogen (Figs 2 and 3), which suggests that AMPK activation may not be strictly associated with growth inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…4A). AMPK activation has been reported to block DNA synthesis (Igata et al 2005), a response that is inconsistent with the actions of a potent mitogen-like PDGF (Fig. 1A).…”
Section: Activation Of Ampk Does Not Inhibit Dna Synthesismentioning
confidence: 96%
“…36 As mentioned above, in the endothelial cell, AMPK activates the PI3K-Akt system, and it has been shown that this antiapoptotic effect takes place through the PI3K-Akt axis. 41 The vascular smooth muscle. We have shown that the growth of the vascular smooth muscle cell stimulated by angiotensin II (AngII) can be inhibited by the activation of AMPK.…”
Section: Function In the Vasculaturementioning
confidence: 99%
“…In the wire injury model of the rat femoral artery, if AMPK is continuously activated by AICAR injection, neointima formation is significantly inhibited, and AMPK inhibits the growth of the vascular smooth muscle, even in vivo. Igata et al 41 revealed that AMPK increases p21cip, which is the cyclin-dependent kinase inhibitor, through inhibition of the phosphorylation of the retinoblastoma gene product (Rb), as well as increased expression/phosphorylation enhancement of p53, and inhibits the cell cycle of the vascular smooth muscle at G1/S. Recently, the presence of a mechanism has shown that the activation of thromboxane A2 receptor promotes hypertrophy of the vascular smooth muscle and activates AMPK ROS dependently.…”
Section: Function In the Vasculaturementioning
confidence: 99%